2004
DOI: 10.1248/cpb.52.178
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anticancer and Antibacterial Activity of Some Novel Mononuclear Ru(II) Complexes

Abstract: The success of cisplatin and related platinum complexes as anticancer agents has stimulated a search for other active transition metal complexes, and ruthenium in particular has attracted the researchers.1) Metal complexes of ruthenium containing nitrogen and oxygen donor ligands are found to be effective catalysts for oxidation, reduction, hydrolysis and other organic transformation.2) The coordination environment around ruthenium plays the key role in stabilizing its different oxidation states and hence dict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…FAB mass spectroscopic data clearly suggested that mononuclear complexes had been formed in each case, the first fragment being due to the [Ru(S) 2 respectively (where S = 1,10-phenanthroline/2,2'-bipyridine and K = r-binh, r-btsz). This type of fragmentation has been reported for [Ru(phen) 2 (nmit)]Cl 2 and [Ru(bpy) 2 (ihqs)]Cl 2 (where phen = 1,10-phenanthroline, bpy = 2,2'-bipyridine, nmit = N-methyl isatin thiosemicarbazone, ihqs = 7-iodo-8-hydroxyquinoline-5-sulfonicacid) 33 . In all cases, the loss of chlorine ions was detected where S = 2,2'-bipyridine/1,10-phenanthroline and K = r-binh, r-btsz.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…FAB mass spectroscopic data clearly suggested that mononuclear complexes had been formed in each case, the first fragment being due to the [Ru(S) 2 respectively (where S = 1,10-phenanthroline/2,2'-bipyridine and K = r-binh, r-btsz). This type of fragmentation has been reported for [Ru(phen) 2 (nmit)]Cl 2 and [Ru(bpy) 2 (ihqs)]Cl 2 (where phen = 1,10-phenanthroline, bpy = 2,2'-bipyridine, nmit = N-methyl isatin thiosemicarbazone, ihqs = 7-iodo-8-hydroxyquinoline-5-sulfonicacid) 33 . In all cases, the loss of chlorine ions was detected where S = 2,2'-bipyridine/1,10-phenanthroline and K = r-binh, r-btsz.…”
Section: Resultssupporting
confidence: 71%
“…The Ru(II) compounds are kinetically more reactive than Ru(III) 32 . We have reported that Ru(II) compounds bearing thiosemicarbazides, 8-hydroxyquinolines, and 4-substituted thiopicolinanalides have in vivo anticancer and in vitro antibacterial activity [33][34][35] . Recently, we have reported that Ru(II) compounds bearing isatin thiosemicarbazones and chloro-fluoro-phenyl imino methyl phenol have in vivo anticancer and in vitro cytotoxic activity 36 .…”
Section: Introductionmentioning
confidence: 99%
“…117 After a brief structureactivity relationship, Meggers and co-workers demonstrated that complex 46 showed the highest cytotoxicity when compared with the other tris-heteroleptic complexes tested. [121,122] During the same year Tan and co-workers demonstrated, for the first time, that Ru(II) polypyridyl complexes with β-carboline alkaloids could simultaneously induce autophagy and apoptosis in HeLa cells through a ROS-mediated mechanism (ROS= reactive oxygen species), which led to mitochondrial dysfunction. 116 However, DNA could be the primary target of this nuclear permeable complex since the cytotoxicity of the complexes directly correlated with their DNA binding affinity.…”
Section: Mechanisms Of Action Involving Direct Interactions With Dnamentioning
confidence: 99%
“…Tumor inhibition by the ruthenium chelates was followed by improvements in hemoglobin, RBC and WBC values. [4] 2. B i s ( 1 , 1 0 -p h e n a n t h ro l i n e / 2 , 2 ′ -b i p y r i d i n e ) ruthenium(II) complexes contain 1-thiocarbamoyl-3,5-diphenyl-2-pyrazoline, 2-(3,5-diphenyl-4,5-dihydropyrazol-1-yl)-4-phenylthiazole, 2-hydroxyphenyl benzimidazole and benzoin thiosemicarbazone ligands coordinated with the metal through nitrogen, sulfur and oxygen atoms.…”
mentioning
confidence: 99%